IL-6, TNF-α, and IL-10 levels/ polymorphisms and their association with type 2 diabetes mellitus and obesity in Brazilian individuals - Rodrigues, Kathryna Fontana; Pietrani, Nathalia Teixeira; Bosco, Adriana Aparecida; Campos, Fernanda Magalhães Freire; Sandrim, Valéria Cristina [UNESP]; Gomes, Karina Braga (Archives of Endocrinology and Metabolism, 2017)
Objective: This study aimed to investigate the association of plasma TNF-α, IL-6, and lL-10 levels and cytokine gene polymorphisms [TNF-α (-308 G→A), IL-6 (-174 C→G) and IL-10 (-1082 A→G, -819 T→C and -592 A→C)] in type 2 diabetes mellitus (T2DM) and obese patients. Subjects and methods: One hundred and two T2DM patients and 62 controls were included in this study. Cytokine plasma levels were measured by the Cytometric Bead Array method. Genotyping was carried out by the polymerase chain reaction. Results: IL-6 levels were significantly different between T2DM patients and controls. Interestingly, IL-6 levels were higher in T2DM patients with BMI > 30 kg/m2 compared with other patients and obese controls. The genotype and allele frequencies were similar between patients and controls. In the T2DM group, the SNP IL-10 -819 T/C showed a difference between the cytokine level and genotypes: IL-10 level in the TT genotype was significantly higher when compared to CC genotype. Conclusions: These results suggest an association between IL-6 levels and obesity, and IL-10 levels and the SNP -819 T/C in T2DM. Knowledge of these variants in T2DM might contribute to a better understanding of the role of inflammation in the etiology and progression of this disease.
Keywords: Interleukin-10; Interleukin-6; Polymorphisms; Tumor necrosis factor-alpha; Type 2 diabetes mellitus